The impact of combination therapy for vulvar lichen sclerosus et atrophicus on the quality of life, psychoemotional profile and sexual function of women - N.I. Chernova; M.I. Proskurina; O.V. Dolya; I.S. Zadorozhnaya (Russian Journal of Clinical Dermatology and Venereology, 2026)
Increasing incidence of vulvar lichen sclerosus et atrophicus (VLSA), chronic nature of the disease, severity of itching, and late complications with changes in the anatomy of the external genital organs lead to the development of a number of disorders, including psychoemotional and sexual dysfunctions, and significantly deteriorate the quality of life of patients. Long-term use of topical glucocorticosteroids (tGCSs) has a number of side effects, requires patient compliance, and does not ensure long-lasting disease remission. This underscores the urgency of the problem and the need for effective approaches to treating this dermatosis. Objective. To examine the impact of combination therapy with VLSA on quality of life, psychoemotional state and changes in sexual function in women. Material and methods. The study involved 45 women diagnosed with VLSA. Based on the received treatment, patients were divided into 2 groups: group 1 (n=24) and group 2 (n=21). At the 1st stage, patients in both groups received topical GCS therapy for 3 months. At the 2nd stage in group 1, tGCSs were used in a “proactive” mode for 2 months, and patients in group 2 underwent combined laser treatment and plasma therapy. The treatment results were evaluated based on the dynamics of itching using a visual analogue scale and data from scales and questionnaires assessing quality of life, levels of anxiety and depression, and female sexual function 3 and 5 months after the therapy initiation. Results. After 5 months of treatment, statistically fewer women in group 2 reported itching (3/14.5%; p≤0.05), a significant improvement in quality of life (1.9±1.02 points; p≤0.05), a significant decrease in anxiety (2±1.16 points; p≤0.05), improved lubrication, satisfaction, and a decrease in dyspareunia compared to group 1. Conclusion. A comprehensive approach to treating women with VLSA using tGCSs, laser procedures and injection techniques significantly improves clinical outcomes and patient quality of life, positively impacting psychoemotional and sexual aspects of a woman’s life, leading to more effective and extensive treatment.